Concepts of Improvement of the Scientific Aspect of the Universe in the System of Continuous Education (Eurasian Journal of Learning and Academic Teaching, 2022)
The article covers the issues of providing students with a unified scientific view of the universe in general secondary schools. Natural sciences physics, chemistry, biology, geography were considered together and a single scientific view of the universe was interpreted.